Correlation between AK7 rs2275554 and male infertility in 421 Vietnamese individuals - Phuong Anh, Nguyen; Van Hai, Nong; Thuy Duong, Nguyen (Academia Journal of Biology, 2022)
Male infertility is a global health problem caused by many factors, including primary ciliary dyskinesia (PCD), multiple morphologic abnormalities of the flagella (MMAF), and genetic factors, in which PCD and MMAF have been reported to be associated with variants in the AK7 gene. So, this study aimed to evaluate the association of polymorphisms AK7 rs2275554 with infertile men in the Vietnamese population. Total DNAs were isolated from 421 samples, including 199 males diagnosed with infertility and 222 healthy individuals having at least one child. All 421 samples were applied for genotyping using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Using statistical methods, we showed that the distribution of their genotypes conformed with Hardy-Weinberg equilibrium (p-values > 0.05). There was no association between polymorphism rs2275554 and male infertility in the Vietnamese population (p-values > 0.05). These findings in this study will contribute to the knowledge base about the underlying genetics of male infertility in the Vietnamese population.